Celebrating the 20th anniversary of the first Xanthomonas genome sequences – how genomics revolutionized taxonomy, provided insight into the emergence of pathogenic bacteria, enabled new fundamental discoveries and helped developing novel control measures – a perspective from the French network on Xanthomonads - Koebnik, Ralf; Cesbron, Sophie; Chen, Nicolas W. G.; Fischer-Le Saux, Marion; Hutin, Mathilde; Jacques, Marie-Agnès; Noël, Laurent D.; Perez-Quintero, Alvaro; Portier, Perrine; Pruvost, Olivier; Rieux, Adrien; Szurek, Boris (Peer Community Journal, 2024)

(untitled)
In this Opinion paper, members of the French Network on Xanthomonads give their personal view on what they consider to be some of the groundbreaking discoveries in the field of molecular plant pathology over the past 20 years. By celebrating the 20th anniversary of the first Xanthomonas genome sequences, they explain how genomics revolutionized taxonomy, provided insight into the emergence of pathogenic bacteria, enabled new fundamental discoveries and contributed to the development of novel control measures. Collectively, such new, genomics-enabled perspective will help to ensure sustainable agriculture and conservation of our environment in the future.